Tetracycline-Dependent Gene Regulation: Combinations of Transregulators Yield a Variety of Expression Windows. (April 2002) - Knott, A.; Garke, K.; Urlinger, S.; Guthmann, J.; Müller, Y.; Thellmann, M.; Hillen, W.
In addition to the originally described Tet transactivator tTA, several variants including transrepressors (tTRs) and reverse transactivators (rtTAs) have been constructed, which we employ here to establish a set of HeLa cell lines carrying different combinations of chromosomally integrated Tet transregulators. We first compare the regulatory properties of these lines using transient transfection of a luciferase reporter gene. Cell lines carrying rtTA-S2 or rtTA-M2 show reduced activity in the absence of dox and higher activation levels in its presence compared to an rtTA line. rtTA-M2 and its synthetic counterpart rtTA2 S -M2 show the same regulation pattern. The replacement of the VP16 activation domain in rtTA-S2 or tTA by p65 leads to slightly reduced expression levels. Combination of an rtTA variant with the transrepressor tTR shows active repression of basal expression without affecting the activation level of the transiently transfected reporter gene. However, if the target gene is also chromosomally integrated, then tTR leads to a further reduction of basal expression and also of the maximal expression level. The results demonstrate that different regulatory windows can be achieved using various transregulators or combinations thereof. Thus, the most appropriate combination of regulators can be chosen depending on the application and cell line desired. We suspect that these properties would also allow the construction of transgenic organisms with preselected expression windows.